Impact of derivative hedging on audit fees in Malaysia - Yan, Andy Rong En (2022)
This study analyses the relationship between auditors’ perceived level of risks due to firms’ hedging activities and its impact on audit fees to determine if the reduced business risks of clients due to hedging will increase auditors’ confidence on clients’ risk profile and thus, charging lower audit fees. Using secondary data collected from Malaysian firms’ annual reports, we find that auditors in Malaysia charges higher audit fees for hedging firms and both Shariah-compliant status and board gender diversity do not have a mediating effect on the relationship between hedging activity and audit fee. As for the audit fee determinants in Malaysia, findings show consistent results for the variables tested except for Big-5 audit fee premium where it is found that the Malaysian Big-5 auditors do charge a higher fee to their clients due to higher audit quality. In conclusion, Malaysian auditors are found to charge higher fees for clients engaged in hedging activities, therefore, the risk-reduction benefit from hedging is muted and over-compensated by the additional audit efforts expended on auditing of derivatives.